Volapük på Hotel Tivoli. Verdenssprogsutopisme i 1880’ernes Danmark - Nygaard, Bertel (Historisk Tidsskrift, 2025)
Volapük in Hotel Tivoli: World Language Utopianism in 1880s Denmark Volapük, the ’world language’ constructed by the German Catholic priest Johann Martin Schleyer in 1879, never became the main language of international communication. Yet, during the late 1880s the Volapük project gained some support, growing into a tiny, transnational language movement that must be understood in the context of a broader trend towards modern cultural internationalism. In other words, the Volapük project was a key chapter in the long-standing quest for a global means of communication as a crucial aspect in the quest for better societies, i.e., what we may term world language utopianism. The Danish Volapük movement shows how such utopian elements circulated transnationally and were actively received and integrated into pre-existing positions within a specific national context. During the initial Danish reception of Volapük in 1885-87 there were close ties between the Volapük cause and the Liberal opposition with its demands for democratization and peace, while Conservatives tended to warn against Volapük as a threat to national languages. The Volapük cause was depoliticized towards the end of the decade as it turned out that initial accusations of socialist implications in the Volapük movement were unfounded (Marxists were mostly critical of Volapük). Nevertheless, small signs of interest in world languages within the growing Socialist labor movement did indicate potential affinities between Socialist conceptions of class internationalism and the longstanding quest for universal means of communication. However, the rapid demise of the Volapük movement in the early 1890s prevented such potentials from developing, and the Esperanto movement carried the mantle of world language utopianism into the following century.